Cetacean conservation and the ethics of captivity. (October 2021) - Muka, Samantha; Zarpentine, Chris
Abstract: Recent decades have seen increasing opposition to cetacean captivity among the general public. However, these discussions often do not address captivity in the context of conservation. At the same time, approaches within conservation biology—compassionate conservation and multispecies justice—call for greater attention to the impact of conservation interventions on individual nonhuman animals. Many questions remain about the implications of these approaches for conservation practice. In this paper, we focus on two recent case studies in cetacean conservation. These case studies highlight how some forms of captivity can contribute to conservation and can help clarify what is at stake between advocates of these approaches and their critics. We argue that some forms of captivity can be ethically justified as part of an ex situ conservation effort, even in cases where they involve risk to individual cetaceans. Highlights: Yangtze finless porpoise and vaquita cases illustrate ethical issues in conservation. Some forms of captivity are important for cetacean conservation. Captivity can sometimes be reconciled with moral duties to individual cetaceans.